Cuadro de mando integral para el control de la gestión en la empresa SUMIPERNOS CÍA. LTDA. de la ciudad de Guayaquil - Mendoza Loor, Fanny Elizabeth (2023)
The present investigation had as its main objective the implementation of the scorecard for management control in the company SUMIPERNOS CÍA. LTDA. in Guayaquil city. It was a bibliographic and field research, in which descriptive, deductive and inductive methods could be incorporated; accompanied by the bibliographic review, tools such as the interview and the survey were used for which The Delphi methodology was used to revalidate the survey, on the other hand, the Likert scale rated from 1 to 5 was executed. The research was developed in 3 phases, the first consisted of making a diagnosis of the current situation of the company SUMIPERNOS CÍA. LTDA. Regarding the control of its management, the management indicators for the measurement of the strategic objectives in the company were then determined and as a last phase, a structuring of the elements of the balanced scorecard was proposed for the management control of the company under study. Before the execution of the project, results were obtained that indicated that the company put into practice the BSC at a level of compliance with its perspectives. It was verified that the CMI contributes to improve the economic income in the reduction of costs and expenses and that the work in the company is streamlined.